Recognition of digital twin city from the perspective of complex system theory: Lessons from Chinese practice - Chuncheng Liu; Ying Tian (Journal of Urban Management, 2023)
Urban system theory seeks to comprehensively capture the complexity of cities. Digital twin cities are "digital mirror images" or symbionts of physical cities, and thus, they form a complex adaptive system. Unlike the reductionist practice of urban informatization and digitalization, digital twins are expected to enable human beings to enjoy the complex beauty of the city for the first time, capable to perceive more information of city and deal with more complex urban problems. Some practical misunderstandings have emerged, however, as a result of simple technical stacking, which is not able to solve urban problems from the root of the problem; has biased thinking about digital twin cities, which treats them as technical tools; and has slowed development of digital twin innovative applications. To solve these problems, we need to draw on basic urban theory. On the basis of complex system theory, in this study, we comprehensively analyzed the characteristics and mechanisms of digital twin cities and constructed a system framework for digital twin cities. We further elucidated the digital twin city and deconstructed it from the perspective of system theory into four subsystems: the planning system, infrastructure system, industrial system, and public service facility system. We then analyzed the subsystem rules and changes in the digital twin city, as well as the principles and development trends that conform to the self-organization and self-adaptive laws of the city.
Keywords: 710; City subsystems; Complex adoptive systems; Digital twin city; Industrial system; Infrastructure system; Planning system; Public service facility system; Systems theory of cities